Development and characterization of a fixed sprinkler with a rotating serrated plate - Antonio Veronez de Sousa, Sérgio; Mota Ramos, Márcio; Chartuni Mantovani, Everardo; Falco Pruski, Fernando; Alves Soares, Antonio (Pesquisa Agropecuaria Brasileira, 1998)
The objective of the present work was to develop serrated deflector plates with rotating movement and to determine the precipitation profile and hydraulics characteristics of one irrigation spray nozzles working with the deflector plates developed. The number of serrates and the diameter used were the same as for the conventional fixed plate. However, serrates were made in helicoydal form to ensure the rotating movement. Plane, concave and convex plates with a ten-degree angle were developed. The concave plate presented the highest wetted radius and consequently the lowest average precipitation rate, specially for lower height of sprinkler positioning. In general, the average precipitation rate decreased as the sprinkler height increased. The precipitation profiles for sprays with the plate were used to simulate the Christiansen Uniformity Coefficient (CUC) for center pivot and linear systems. The CUC increased as the sprinkler spacing decreased. All the CUC were higher than the minimum recommended. There was no difference between the CUC values for the different plates.